Foreign Direct Investment and its Theoretical Approaches - Kumar, Dinesh (Journal of Commerce and Trade, 2009)
Multinational Enterprises enter the host countries via FDI, portfolio investment, export or through leasing of technology and patents (Frank, 1980).While considering cross border investment, it is important to distinguish between FDI and Portfolio Investment. Portfolio Investment involves passive holding of securities and other financial assets, which does not reflect active management or control or both of the security’s holders. High rates of return and reduction of risk through geographic diversification positively influence it. The management dimension is what distinguishes FDI from Portfolio Investment in foreign stocks, bonds and other financial instruments Several theories on FDI as envisaged above basically cover two distinct approaches: microeconomic approach approach (Buckley and Casson, 1976). While microeconomic approach to FDI flow attempts to explain why firms in one country are successful in penetrating into other markets, the macroeconomic approach (Buckley and Casson, 1976) tries to examine why firms look for international expansion.